Watson Alan, The Law of Obligations in the Later Roman Republic - Rozwadowski, Władysław (Czasopismo Prawno-Historyczne, 1967)
Recenzja: Alan Watson, The Law of Obligations in the Later Roman Republic, Oxford 1965, At the Clarendon Press, ss. XII + 295.